The efficacy of psychological capital training on positive emotions and academic optimism among students - Masoumeh Besharati Pour; Alireza Hajiyakhchali; Manigah Shehni Yailagh; Gholamhossien Maktabi (مجله علوم روانشناختی)
Background: As students’ progress through their formal education, they experience a range of emotions - both positive and negative-associated with their learning. Alongside these emotions, academic optimism is a crucial cognitive factor that affects academic performance. While there has been much research on the effectiveness of psychological capital, there is a lack of studies that explore its impact on academic variables in students. Therefore, this study aims to investigate whether psychological capital training can improve students' educational emotions and optimism. Aims: The current research aimed to determine the effectiveness of psychological capital training on the positive emotions and academic optimism of students. Methods: The research method was a quasi-experimental design, with a pre-test and post-test for a control group. The statistical population consisted of all male middle school students in Bandar Imam Khomeini during the 2023-2024 academic year. The statistical sample included 60 students, selected through multistage cluster random sampling, from three schools out of all first middle schools for boys. They were randomly assigned to either the experimental or control group (each group comprised 30 students). All participants completed the Pekrun et al. (2002) Academic Emotions Questionnaire and the Schnen-Moran et al. (2013) Academic Optimism Questionnaire as a pre-test. Subsequently, the experimental group received a psychological capital intervention based on Luthans et al. (2007) for ten 90-minute sessions, a group setting. After the intervention, both groups completed the questionnaires as a post-test. The data were analyzed using multivariate and univariate covariance analysis with the SPSS-25 statistical software. Results: The results of multivariate covariance analysis of the data showed that psychological capital training has a significant effect on positive academic emotions and academic optimism of students. (p< 0.01). Also, the results of univariate covariance analysis showed that psychological capital training had a significant effect on the components of hope and pride from positive academic emotions and academic emphasis, students' trust in teachers, and school belongingness from the components of academic optimism. But it was not significant on the Pleasure of learning of component from positive emotions(p> 242). Conclusion: Based on the research findings, it seems that psychological capital training can serve as an effective intervention to enhance the positive educational emotions and academic optimism of students.